2016
DOI: 10.3390/molecules21111428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of the Flavonoid Natural Product Dryocrassin ABBA against Staphylococcus aureus Sortase A

Abstract: Abstract:The intractability of bacterial resistance presents a dilemma for therapies against Staphylococcus aureus (S. aureus) infection. Effective anti-virulence strategies are urgently needed, reflecting the proliferation of resistant strains. Inhibitors of sortase A (SrtA), enzymes that anchor virulence-related surface proteins, are regarded as promising candidates for countermeasures against bacterial infections. In the present study, the inhibitory effect of dryocrassin ABBA (ABBA) against SrtA and its mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For this reason, therapeutic agents targeting virulence factors, such as SrtA and Hla, which do not threaten survival, may not lead to the development of resistance as quickly as conventional antibiotics typically do, and this will have important implications for S. aureus infection. Some agents targeting S. aureus SrtA or Hla have been found previously (Liu et al, 2015 ; Zhou et al, 2015 ; Zhang et al, 2016 ). However, as these compounds are targeted only at one kind of virulence factor, the limitations for clinical treatment will certainly exist.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For this reason, therapeutic agents targeting virulence factors, such as SrtA and Hla, which do not threaten survival, may not lead to the development of resistance as quickly as conventional antibiotics typically do, and this will have important implications for S. aureus infection. Some agents targeting S. aureus SrtA or Hla have been found previously (Liu et al, 2015 ; Zhou et al, 2015 ; Zhang et al, 2016 ). However, as these compounds are targeted only at one kind of virulence factor, the limitations for clinical treatment will certainly exist.…”
Section: Discussionmentioning
confidence: 88%
“…Soon after SrtA was discovered and cloned, many studies reported that the in vivo inhibition of SrtA could be measured. Subsequently, a number of SrtA inhibitors, including natural products and synthetic small molecules, among others, were identified (Clancy et al, 2010 ; Zhang et al, 2014 , 2016 ; Lin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, flavonoids exhibited strong sortase inhibitory activity, which is an enzyme that is responsible for modulating the attachment ability of cells to host tissue and the production of surface protein virulence factors to the peptidoglycan cell wall layer of Gram-positive bacteria such as Streptococcus mutans and Streptococcus pneumoniae [38,40]. The inhibitory effect on the S. aureus sortase A activity of the dryocrassin ABBA flavonoid has been studied [41], and similar activity was also observed with the application of isovitexin at an IC 50 of 28.98 mg/L [42]. Therefore, it is conceivable that the anti-biofilm potential of the extracts may be related to the ability of their phytochemical components to inactivate bacterial adhesins and enzymes altering the cell membrane, cell-substratum interactions, adherence phase, and biofilm maturation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, small-molecular inhibitors of sortase A have been reported among the derivatives of diarylacrylonitrile [ 5 , 6 ], aryl(β-amino)ethyl ketone [ 7 ], rhodanine, pyridazinone, pyrazolethione [ 8 ], morpholinobenzoate, aryl 3-acryloamides [ 9 , 10 ], dihydro-β-carboline [ 11 ], benzo[d]isothiazol-3(2 H )-one-adamantane amine [ 12 ], 3,6-disubstituted triazolothiazole [ 13 ], 2-phenylbenzofuran-3-carboxamide [ 14 ], 2-phenylbenzo[d]oxazole-7-carboxamide [ 15 ], 2-(2-phenylhydrazinylidene)alkanoic acid [ 16 ], indolethiazolidine [ 17 ], pyrrolomycin [ 18 ], 2-phenylthiazole [ 19 ], 2,5-disubstituted thiadiazole [ 20 ], thiadiazolinedione [ 21 ], disulfanylbenzamide [ 22 ], and 1,2,4-oxadiazole topsentin analogs [ 23 ]. Furthermore, several inhibitors for sortase A have been identified among natural products such as β-sitosterol-3-O-glucopyranoside [ 24 ], berberine chloride [ 25 ], bis(indole)-alkaloid [ 26 ], isoaaptamine [ 27 ], flavonoids (kurarinol [ 28 ], myricetin [ 29 ], quercitrin [ 30 ], morin [ 31 ], eriodictyol [ 32 ], acacetin [ 33 ], 7-hydroxy-6-methoxy-flavanone and formononetin [ 34 ], dryocrassin ABBA [ 35 ]), curcumin [ 36 ], maltol-3-O-(4′-O-cis-p-cumaroyl-6′-O-(3-hydroxy-3-methylglutaroyl)- β -glucopyranoside [ 37 ], skyrin [ 38 ], aspermytin A [ 39 ], natural naphthoquinones [ 40 ], isovitexin [ 41 ], coumarines [ 42 ], taxifolin [ 43 ], erianin [ 44 <...>…”
Section: Introductionmentioning
confidence: 99%